The Conundrum of Defining and Prosecuting Terrorism: A Review of United Kingdom and International Responses - Singh, Charanjit (International Journal of Criminology and Sociology, 2023)
Terrorism presents one the biggest criminal justice postmodern challenges worldwide. The way criminal justice systems proact and react to mitigate and prevent such criminality raises a plethora of legal, socio-political, and strategic hurdles relating to how terror crime is defined, the human rights of the accused, protecting due process when using secret courts, the use of special advocates, the use of national security courts, civil rights i.e., freedom of association, cross-jurisdictional information sharing, and the requirement or right to prosecute etc. In this article, which is influenced by criminological theory, the definition of terror crime in the United Kingdom and at an International level is examined to ascertain whether common definitional elements exist, and the complex and competing local and International interests that are being balanced in preventing and/or prosecuting such crime.